When Kopiko and K-Pop Get Married: Creative Brand Publicity through Drama Series and Beyond - Yusdiaana, Deni; Alchoiri, Muhammad Firrizqi; Iswanto, Haifa Firyal (Jobmark: Journal of Branding and Marketing Communication, 2026)
Brand and product placement, an increasingly popular marketing strategy, has been masterfully executed by Kopiko, an Indonesian coffee candy brand. This article analyzes how Kopiko successfully implemented a Creative Brand Publicity (CBP) strategy through product placement in the Korean drama Vincenzo. With a descriptive-qualitative approach and case study method, this study found how Kopiko leveraged the drama's popularity to increase brand awareness and expand its reach to international markets. Data was collected through in-depth document searches of news, articles, Kopiko marketing materials, and related social media content. Additionally, digital documentation in the form of screenshots of scenes featuring Kopiko products in the drama was also analyzed. Kopiko seamlessly integrated its product into Vicenzo's storyline, creating compelling brand exposure without disrupting the viewing experience. This strategy has not only increased Kopiko brand awareness and drove sales, especially in international markets, but also serves as a testament to the success of innovative brand marketing strategies seeking to expand market reach and strengthen brand image.